2020
DOI: 10.1002/anie.202010651
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Durable, and Recyclable Metal‐Free Catalysts for Highly Efficient Conversion of CO2 to Cyclic Carbonates

Abstract: As eries of highly active organoboron catalysts for the coupling of CO 2 and epoxides with the advantages of scalable preparation, thermostability,a nd recyclability is reported. The metal-free catalysts show high reactivity towards aw ide scope of cyclic carbonates (14 examples) and can withstand ahigh temperature up to 150 8 8C. Compared with the current metal-free catalytic systems that use mol %c atalyst loading, the catalytic capacity of the catalyst described herein can be enhanced by three orders of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 99 publications
1
75
2
2
Order By: Relevance
“…97 On the other hand, the group of Wu reported a bifunctional organoboron organocatalyst able to achieve full conversion and excellent yield of GC at remarkably low (0.02 mol%) catalyst loading though under somewhat harsher reaction conditions (120°C, 20 MPa CO 2 ). 98 In the latter case, mechanistic studies indicated that the boron acts as a Lewis acid and activates the oxirane ring near a closely positioned ammonium iodide unit (Scheme 8). Lastly, Kleij et al showed that DBU can promote the formation of GC from Gly and other epoxy alcohols through the formation of a hemicarbonate intermediate under mild reaction conditions (45°C, 1 MPa CO 2 ).…”
Section: Glycerol Carbonate From Glycidolmentioning
confidence: 99%
“…97 On the other hand, the group of Wu reported a bifunctional organoboron organocatalyst able to achieve full conversion and excellent yield of GC at remarkably low (0.02 mol%) catalyst loading though under somewhat harsher reaction conditions (120°C, 20 MPa CO 2 ). 98 In the latter case, mechanistic studies indicated that the boron acts as a Lewis acid and activates the oxirane ring near a closely positioned ammonium iodide unit (Scheme 8). Lastly, Kleij et al showed that DBU can promote the formation of GC from Gly and other epoxy alcohols through the formation of a hemicarbonate intermediate under mild reaction conditions (45°C, 1 MPa CO 2 ).…”
Section: Glycerol Carbonate From Glycidolmentioning
confidence: 99%
“…Finally, ring closure occurred by the alkyl carbonate attack on the terminal carbon atom to produce the corresponding cyclic carbonates and the boronate ester (B 4a ) catalyst. [ 5,18–20 ] After the release of ECH, the boronate ester (B 4a ) catalyst is regenerated and the catalysis continues in the same way.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, until recently boron compounds are very rarely preferred as a potent class of organocatalysts for chemical fixation of CO 2 to highly demanding cyclic carbonates. [ 17–21 ] Therefore, we think that boronate esters as an efficient catalyst will remove some restrictions in the chemical fixation of CO 2 to valuable chemicals such as cyclic carbonate and polycarbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent organoboron compounds are of increasing importance for capturing and reacting with small molecules [34,35] . The boron-mediated conversion of carbon dioxide to cyclic carbonates [36] and copolymers [Figure 2A] [37] and to formate [Figure 2B] [38,39] with bifunctional borylated catalysts is a rapidly evolving area of chemical catalysis oriented towards green chemistry.…”
Section: Helical Boron-containing Materials [Figurementioning
confidence: 99%